Cryptography and coding : 16th IMA International Conference, IMACC 2017, Oxford, UK, December 12-14, 2017, Proceedings /: 16th IMA International Conference, IMACC 2017, Oxford, UK, December 12-14, 2017, Proceedings. (2017) - Unknown
No abstract available